Pre and post-merger impact on financial performance of Malaysian banks / Intan Shairah Yusof - YUSOF, INTAN SHAIRAH (Faculty of Business Management, 2017)
This paper endeavors to examine the pre and post-merger impact on financial performance of Malaysia’s local banks. To accomplish this objective, the research methods used to compare pre-post-merger financial performance is comparison and analysis of ratios to compare the performance of Malaysian banks during the pre-merger period (1999-2002) and post-merger period (2003-2005). In addition, a comparative study will be carried out to show possible impact between the pre and post-merge of local banks from the perspective of performance and profitability. This paper will analyze the impact of merger on banks’ profitability that measured by liquidity ratio, leverage and shareholder’s wealth. For this analysis, a panel data regression methodology will be applied to study the performance of these commercial banks within Malaysian’s local banks. Financial ratios are collected for a total of 5 (five) local banks covering a period between 1999 and 2006. Based on the result, 4 out of 6 variables are significant but 2 of it is negative relationship toward profitability during the pre-merger year. Meanwhile, the results for post-merger have only one significant result of variables toward profitability and it has a positive relation.